2016
DOI: 10.1111/imj.13051
|View full text |Cite
|
Sign up to set email alerts
|

Recent treatment advances in Hodgkin lymphoma: a concise review

Abstract: The majority of patients with Hodgkin Lymphoma enjoy durable remissions following front-line treatment. This typically involves combination chemotherapy with or without radiotherapy. A significant minority of patients experience relapsed/refractory disease, of whom only approximately half can be 'salvaged' with conventional second-line treatments. Until recently, for those patients either failing or who are not fit for salvage, there have been few curative alternatives. Furthermore, there is a significant risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Gains in SDI are likely to operate through many pathways, including improved access to health care, public health programmes, and social and welfare policy. Advances in treatment are well documented for various causes, including HIV/AIDS, 30 , 31 , 32 ischaemic heart disease, 33 , 34 , 35 , 36 , 37 and various cancers, 38 , 39 , 40 including breast, 41 , 42 , 43 testicular, 44 and Hodgkin's, 45 yet for other causes, such as oesophageal cancer and interpersonal violence, the policies, programmes, and interventions responsible for declining risk-deleted death and DALY rates are less clear than for the aforementioned causes. Improvement of understanding of the risk-deleted rates in cause-specific mortality and disease burden will strengthen the evidence base for intervention effectiveness, the role of medical care access in addressing disease burden, and the importance of other social and welfare policies.…”
Section: Discussionmentioning
confidence: 99%
“…Gains in SDI are likely to operate through many pathways, including improved access to health care, public health programmes, and social and welfare policy. Advances in treatment are well documented for various causes, including HIV/AIDS, 30 , 31 , 32 ischaemic heart disease, 33 , 34 , 35 , 36 , 37 and various cancers, 38 , 39 , 40 including breast, 41 , 42 , 43 testicular, 44 and Hodgkin's, 45 yet for other causes, such as oesophageal cancer and interpersonal violence, the policies, programmes, and interventions responsible for declining risk-deleted death and DALY rates are less clear than for the aforementioned causes. Improvement of understanding of the risk-deleted rates in cause-specific mortality and disease burden will strengthen the evidence base for intervention effectiveness, the role of medical care access in addressing disease burden, and the importance of other social and welfare policies.…”
Section: Discussionmentioning
confidence: 99%
“…Among the differences in these patients' survival rates by decade of diagnosis, differences in the 10-year survival rates were most pronounced, suggesting that the long-term improvements in survival likely were due to improvements in treating the primary disease and preventing or delaying disease progression and recurrence. [29][30][31][32][33] In contrast, among AYA survivors of melanoma, the long-term survival rates of those diagnosed in the 1970s, 1980s, or 1990s did not differ significantly, whereas those survivors diagnosed in the 2000s had improved early survival. It is important to note that, compared with those diagnosed in earlier decades, survivors of melanoma who were diagnosed in the 2000s had a higher rate of localized disease at the time of presentation, potentially skewing outcomes, because the current study data demonstrated that survivors who presented with local melanoma had significantly better survival than those who presented with regional or metastatic disease (see Supporting Fig.…”
Section: Discussionmentioning
confidence: 89%
“…[16][17][18][19][20] It is also showing promise in the treatment of Hodgkin's lymphoma. [21] With their outstanding efficacy in many cancers, their use is likely to increase in clinical practice. They are effective in younger as well as older age groups.…”
Section: Metastatic Malignancies and Immune Modulationmentioning
confidence: 99%